El patrimonio cultural como derecho: el caso ecuatoriano (Tema Central) - Mejía Salazar, Álvaro Renato (2014)
When it comes to human rights, the first thoughts that come to mind are the rights to life, liberty or equality, among others, which possess the concept of being fundamental. Commonly, culture and heritage are not usually considered as rights; however, as well as there is the right to own legal identity, there is also the right to enjoy a cultural identity. This paper deals precisely with the study of culture and cultural heritage as a human right. Cultural heritage’s meaning concept is analyzed, its enclosure between fundamental rights and the way that it should be protected, essentially by the State. The Ecuadorian case is also analyzed around their legislation and cultural management, in order to assess the treatment that this right has been received in the country.